2014
DOI: 10.1590/s0100-83582014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Sorghum sudanense and Eleucine indica in the soybean and corn cultivation

Abstract: -The natural infestations are composed of numerous species that compete for environmental resources such as water, light, nutrients and space. The objective of this study was to evaluate the interference of mixed infestations Sorghum sudanense (sudangrass) and Eleusine indica (goosegrass) in the presence of soybean and corn. The experimental design was completely randomized with four replications and the experimental units consisted of plastic pots with a volume capacity of 8 L. The treatments were association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This fact was also reported by Christoffoleti and Victoria Filho (1996) when studying maize competition with pigweed. Rizzardi and Wandscheer (2014) observed that the species that demonstrate greater competitiveness suffer more from intraspecific competition than from interspecific competition, as plants with greater competitive capacity are usually harmed due to lack of space or environmental resources.…”
Section: Resultsmentioning
confidence: 99%
“…This fact was also reported by Christoffoleti and Victoria Filho (1996) when studying maize competition with pigweed. Rizzardi and Wandscheer (2014) observed that the species that demonstrate greater competitiveness suffer more from intraspecific competition than from interspecific competition, as plants with greater competitive capacity are usually harmed due to lack of space or environmental resources.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Ma et al (2015) demonstrated that goosegrass at a density of 4 plants m −1 per row significantly reduced cotton yields by 20 to 27%. Rizzardi and Wandscheer (2014) documented that E. indica was more competitive than Sorghum sudanense in mixed infestations with corn but in contrast S. sudanense was more competitive than E. indica, in mixed infestations with soybean.…”
Section: Abstrakmentioning
confidence: 99%